LH and Prolactin interrelation with respect to estrus in buffaloes - SINGH, J K; LUDRI, R S; PANDITA, SUJATA (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to find out the association between LH and Prolactin hormones during different seasons with respect to the estrus. Blood samples were collected from six normal cycling buffaloes at 4 hr intervals up to 36 hrs from the start of estrus. The level of hormones in plasma was estimated by RIA. The average concentration ofprolactin ranged from 7.09 to 26.37, 0.31 to 2.71 and 3.26 to 19.59ng/ml during hothumid, cold and warm season, respectively and that ofLH ranged from 0.32 tolS.70, 0.27 to 13.41 and 0.39 to 4.83ng/ml, respectively. The individual animal data indicated that in majority of estrus LH peak was associated with concomitant rise in Prolactin. The findings suggest a positive relationship of LH and prolactin release during the estrus.